Apprenticeship System and Labour Supply of Electrical Installation Artisans in Enugu State, Nigeria - Ogbuanya, Theresa Chinyere; Chukwu, Clement; Orji, Chibueze Tobias (Journal of Technical Education and Training, 2020)
The main purpose of the study was to assess the apprenticeship system and labour supply of electrical installation artisans in Enugu State. This survey study was carried out in Enugu State of Nigeria which involved 234 apprentices of electrical installation. A structured questionnaire was used for data collection. The instrument was face-validation by three experts and pilot tested on 15 apprentices in Anambra to determine its reliability. Cronbach Alpha reliability method was used to establish the internal consistency of the instrument and it yielded the overall reliability coefficients of 0.87. After the data collection, mean, standard deviation and t-test were used to answer the research questions and null hypotheses that guided the study. The study found that 14 modalities were needed for the admittance of apprentices, 10 attraction packages were found for facilitating enrolment into apprenticeship system, 11 motivation indices were found for apprentices in electrical installation, there was no significant difference between the mean responses of early apprentices and late apprentices on the attraction of apprentices’ enrolment into apprenticeship system, and on motivation indices and instructional modalities. It was, therefore, recommended that the Government should grant loans to trained artisans to acquire essential equipment for the training and enterprising thereby boosting their output capacities.